Agripreneurship for employment and empowerment of women in rural areas - Valentina, G. (Golla) (2015)
Contributed articles.
Includes bibliographical references and index.
Keywords: Women in agriculture -- Government policy -- India; Businesswomen -- India -- Economic conditions; Rural women -- Employment -- India